Children Disease Diagnosis System Using Forward Chaining Method (Sistem Pakar Diagnosa Penyakit Ayam Dengan Menggunakan Metode Forward Chaining) - Hari Marfalino; Mutiana Pratiwi; Randi (Universitas Putra Indonesia YPTK Padang, 2019)
Expert systems are widely used in various types of fields, one of which is in the field of animal husbandry. The number of chicken farms that appear is not comparable with information and knowledge about raising chickens, so dependence on experts is the only solution in handling chicken disease problems. Expert systems can be a solution to problems that arise in terms of handling chicken disease. Expert systems that are built using the forward chaining method can work like an expert who can deduce the problem from the symptoms given. With the existence of an expert system, dependence on experts is no longer a solution in dealing with the problem of chicken disease, because ordinary people can also provide action like an expert.